Occupational exposures and chronic kidney disease: Possible associations with endotoxin and ultrafine particles. Issue 1 (17th November 2015) - Sponholtz, Todd R.; Sandler, Dale P.; Parks, Christine G.; Applebaum, Katie M.
Abstract : Background: Chronic kidney disease (CKD) carries a high public health burden yet there is limited research on occupational factors, which are examined in this retrospective case‐control study. Methods: Newly diagnosed cases of CKD (n = 547) and controls (n = 508) from North Carolina provided detailed work histories in telephone interviews. Unconditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: There was heterogeneity in the association of CKD and agricultural work, with crop production associated with increased risk and work with livestock associated with decreased risk. Work with cutting/cooling/lubricating oils was associated with a reduced risk. CKD risk was increased for working in dusty conditions. Conclusions: CKD risk was reduced in subjects with occupational exposures previously reported to involve endotoxin exposure. Further, exposure to dusty conditions was consistently associated with increased risk of glomerulonephritis across industry, suggesting that research on CKD and ultrafine particulates is needed. Am. J. Ind. Med. 59:1–11, 2016. © 2015 Wiley Periodicals, Inc.